RANCANG BANGUN SISTEM KENDALI PERAWATAN TANAMAN ANUBIAS NANA PADA AQUASCAPE BERBASIS INTERNET OF THINGS - Ahmad Abdur Rozaq; Anton Breva Yunanda; Mochamad Sidqon; Agung Kridoyono (Jurnal Rekayasa Sistem Informasi dan Teknologi, 2025)
This research focuses on the development of an Internet of Things (IoT)-based control system to support the maintenance of Anubias Nana plants in an aquascape environment. The system is designed to simplify aquascape care, which often faces challenges in maintaining plant health, particularly amid users’ busy routines and limited understanding of plant needs. This system integrates a pH sensor and a DS18B20 temperature sensor to monitor environmental conditions in real-time. Nutrient solution is dispensed using a peristaltic pump based on a predefined schedule managed by an RTC module, while additional peristaltic pumps are used to regulate the pH level. The aquarium heater and cooling fan are automatically controlled based on sensor data, while the LED lighting is scheduled using the RTC to maintain consistent illumination within the aquascape. The research began with the design of both hardware and software components to optimize environmental parameter settings. This system offers an innovative solution for aquascape users to maintain plant health over the long term while improving maintenance time efficiency. With the implementation of IoT technology, aquascape users can enjoy a more practical and efficient maintenance experience without losing control over their aquascape's environmental conditions. This research is also expected to serve as a reference for future developments in automated aquascape plant care systems.